Extraction and characterization of pectins from peels of criolla oranges (Citrus sinensis): Experimental reviews - Ruano, Paula (2019)
The citriculture in the international field is important not only for its nutrient and vitamin characteristics but also for its valuable source of raw materials to obtain pectin, since it was found in the internal and external parts of the citrus peel. In our country, there are several varieties of orange, from which you can obtain by-products other than juice, such as essential oils, fertilizers, concentrates, and pectin. Pectin has different uses in the pharmaceutical industry for the preparation of suspensions, emulsions, cosmetics, capsules, etc. In the food industry, it is used as a film in packaging, thickener, and gelling agent in the manufacture of jellies and preserves, in wines as dehydrating plant tissues, in milk to precipitate casein, etc. The pectin extraction was carried out by basic or acid hydrolysis and then proceeds to purify and clarify. Once purified, the pectin was characterized in aqueous solution to determine its physicochemical properties such as molecular weight, hydrodynamic radius, hydration value, shape factor, etc. Thermal and mechanical characterizations were also performed, to assess its ability to form films.